Speaking Out on Sexualized Violence Through Artistic Storytelling in Post-conflict Northern Ireland - Van Ooijen, Anna-Lea (Violence against women, 2024)
Directly related to The Troubles, sexualized violence has been largely ignored, yet continues to affect significant numbers of individuals in Northern Ireland today. This article analyzes various women's stories concerning sexualized violence shared in testimonial theater projects in Northern Ireland. We argue that (a) artistic storytelling about sexualized violence in theater projects can be a tool to release individuals and the collective from the (normalized) silence surrounding these violent acts and (b) it is an epistemological transformative method of inquiry to address these acts with the aim of eliminating them.